Reactive oxygen species and myocardial apoptosis - Zhao, Zhi-Qing (Henry Stewart Talks, 2007)
Reactive oxygen species, Ischemia/reperfusion, Necrosis, Apoptosis, Infarct size, Mitochondrial calcium overload, Mitochondrial dysfunction, Cytochrome c release from mitochondria, MAPK kinases, NFkappaB, TNFalpha, IL6, Caspases, Antioxidant, Postconditioning
Archived at 2018/01/31